Haploidentical peripheral blood stem cell transplantation combined with unrelated cord blood in hematologic malignancy patients: A report of 80 cases - Zeng, Cong; Chen, Yan; Hua, Juan; Liu, Yi; Cheng, Ting-ting; Ma, Xia; Chen, Xu; Wang, Shi-yu; Xu, Ya-jing (Frontiers in Immunology, 2022)
The outcomes of 80 patients with hematologic malignancies who received haploidentical peripheral blood stem cell transplantation (haplo-PBSCT) combined with unrelated cord blood (UCB) from March 2017 to June 2020 were analyzed in this retrospective study. Anti-thymocyte globulin(ATG) was administered at a dose of 7.5 mg/kg. The median time for neutrophil and platelet engraftment was 13(range: 8-22) days and 14(range: 8-103) days, respectively. The 30-day cumulative incidence of neutrophil engraftment was 100%, and the 100-day cumulative incidence of platelet engraftment was 95%. All patients achieved complete haploidentical peripheral blood stem cell engraftment, and no cord blood chimerism was observed. The cumulative incidence of grades II-IV and grades III-IV acute graft-versus-host disease (aGVHD) on 100-day was 26.3%(95%CI: 17.2%–36.3%) and 5.0%(95%CI: 1.6%–11.4%), respectively. The estimated cumulative incidence of chronic GVHD (cGVHD) and moderate-severe cGVHD at 3-year was 43.3%(95%CI: 31.6%–54.4%) and 16.0%(95%CI: 8.7%–25.2%), respectively. The estimated 3-year cumulative incidence of relapse and non-relapse mortality was 18.8%(95%CI: 10.0%–29.7%) and 17.8%(95%CI: 9.9%–27.5%), respectively. The estimated 3-year probabilities of overall survival, disease-free survival, GVHD/relapse-free survival were 77.6%(95%CI: 68.3%–88.1%), 63.4%(95%CI: 52.6%–76.5%), and 55.5%(95%CI: 44.8%–68.7%), respectively. These satisfying results suggested that haplo-PBSCT combined with UCB is an alternative transplantation protocol for hematologic malignancies.